Darwinism and Portmannism: The Clash of Incomparable Biological Paradigms? - Jaroš, Filip (Teorie vědy / Theory of Science, 2010)
The article focuses on the possibility of the cultivation of biology inspired by the work of biologist A. Portmann. Insight into the problem is to some extent limited to the Czech language area, where Portmann’s ideas are relatively well established. The paper analyses the causes of latent tension between so-called Darwinists and Portmannists. There are a lot of misunderstandings at this point. First of all, it must be considered that Portmann didn’t disregard Darwin’s theory. The aim of the article is to show that Portmann’s ideas transcend a traditional Darwinian reduction of a life form to adaptive function. Divergence of these schools of thought comes from different opinions on the nature of science. The paper shows how dissimilarities of aims and means of biological exploration lead to different conclusions about living creatures. For research growing out of Portmann’s ideas, it is necessary not to consider Darwinism as a competitor, but as a thought-provoking partner for a dialogue.